Dampak Efektivitas Sistem Informasi Akuntansi: Pengaruh Teknologi Informasi dan Kualitas Sumber Daya Manusia Terhadap Kinerja Perusahaan - Ilham Audy Rivand; Suwandi Suwandi (Journal of Culture Accounting and Auditing, 2023)
This study aims to prove the influence of information technology and the quality of human resources on the company's performance at PT. PLN Pesero Tbk. UP3 Gresik which is mediated by the effectiveness of the accounting information system. This study uses a questionnaire containing questions related to information technology, the quality of human resources, company performance and the effectiveness of accounting information systems using a Likert scale measurement. The questionnaire was addressed to employees of PT. PLN Pesero Tbk. UP3 Gresik. The results of the questionnaire were tested using SmartPLS 3.0 and present the results that information technology does not affect the effectiveness of accounting information systems, the quality of human resources affects the effectiveness of accounting information systems, the effectiveness of accounting information systems affects company performance, information technology affects company performance, the quality of human resources does not affect the company's performance. Furthermore, the effectiveness of accounting information systems is able to mediate the relationship between the quality of human resources and company performance but is unable to mediate the relationship between information technology and company performance.